Kinetics and mechanism of crystallization of borophosphate glasses of the ZnO-B2O3-P2O5 system - Mošner, Petr; Koudelka, Ladislav (Univerzita Pardubice, 1999)
Borophosphate glasses of the ZnO-B2O3-P2O5 system were prepared by cooling the melt from 1230 °C. Their crystallization was studied by DSC and X-ray diffraction. The crystallization takes place mostly at 600-800 °C giving at least two crystalline phases with BPO4 as one of the products. The kinetics of the crystallization of borophosphate glass 58.3ZnO-8.3B2O3-33.4P2O5 can be describede be the Šesták-Berggren model, while that of 50ZnO-50B2O3 is better described by the Johnson-Mehl Avrami model. The analysis of the shape and position of the crystallization peak for different sizes of glass powders lead to the conclusion that surface crystallization prevails for the borophosphate glass, While for the borate glass surface crystallization dominates only when the particle size is under 300 um, but internal crystallization prevails in the bulk glass.
Keywords: borofosfátová skla; krystalizace; kinetika krystalizace; reakční mechanismy